Tridimensional parametric model for prediction of structural safety of existing timber roofs using laser scanner and drilling resistance tests. (15th April 2019) - Cuartero, Jaime; Cabaleiro, Manuel; Sousa, Hélder S.; Branco, Jorge M.
Highlights: Heritage timber structures with intricate shapes, variable section and decay. Combination of laser scanner and drilling resistance tests to analyse existing structures. Volume calculation by laser scanner of complex timber roof structures. 3D parametric models to assess safety of timber structures. Structural analysis dependant of decay evolution on time. Abstract: Heritage timber structures are found worldwide evidencing intricate configurations, not only due to the arrangement between elements, which sometimes leads to complex connections with hidden elements, but also due to elements with variable cross-sections and often with signs of decay. Due to its historical value, the structural safety of these structures must be assessed periodically and the conservation state verified. The presence of decay and the resulting reduction of effective cross-section must be assessed both at the present time as well as its probable evolution in the future if no intervention is made. Due to this need, in the present work, a methodology is proposed to analyse the structural safety of timber structures using tridimensional parametric models where the geometry of the cross-section of each element is a variable regarding the presence of decay. The model allows to determine the structure's volume more accurately, to identify the present condition of the structure and make predictions of possible future decay scenarios. Information obtained by laser scanner and drilling resistance tests are considered as prior information for the model. As to demonstrate the validity of the proposed methodology, the creation of a tridimensional parametric model is applied to a case study corresponding to the timber ceiling structure of the Knights' Room of the Convent of Christ in Portugal.